Precipitation behavior of iron and silicic acid when mixing acidic and weakly alkaline geothermal waters at the Hatchobaru geothermal power plant, Oita, Japan. (September 2022) - Juhri, Saefudin; Yonezu, Kotaro; Inoue, Hitoshi; Kiyota, Yumi; Ohshima, Shogo; Uemura, Hideo; Uchiyama, Noriaki; Ueda, Akira; Yokoyama, Takushi
Abstract: This study investigated the precipitation behavior of silicic acid (Si) and iron (Fe) when acidic and weakly alkaline geothermal waters were mixed at various mixing ratios (R) (the proportion of the acidic geothermal water, which ranged from 1 to 9) at 85 ˚C under an oxidizing atmosphere at the Hatchobaru Geothermal Power Plant in Japan. The pH and total Fe concentration of the acidic and weakly alkaline geothermal waters were 2.8 and 8.7 at 25 ˚C and 6.5 and 0.5 ppm, respectively. The pH of the mixed geothermal waters at 85 ˚C ranged from 8.11 to 3.30. Although Si precipitated after they were mixed at R of 1 to 4, Fe precipitated immediately after mixing, independent of R. The amount of Fe precipitated also increased with increasing R (thus increasing the Fe initial concentration). The precipitates were divided into two groups based on their chemical composition: those with a high Si/Fe atomic ratio in the range of 100 to 150, found at R of 1 to 4, and those with a Si/Fe atomic ratio lower than 10, found at R of 5 to 9. Silicic acid polymerized after they were mixed at R between 1 and 3 and the polymerization was not observed at R above 4. Fe was present as colloidal hydrous ferric oxide (HFO) and hydrolyzed species of Fe 3+ in the acidic geothermal water. From these results, it may be concluded that the precipitates with a high Si/Fe atomic ratio were formed due to the aggregation of polysilicic acid particles with Fe at R from 1 to 3, whereas the precipitates with low Si/Fe atomic ratios were formed owing to the aggregation of HFO bonding monosilicic acid because of the sudden increase in pH at all R. There was a large amount of precipitate (the sum of Fe and Si mmol) at R from 1 to 4, indicating that delaying the polymerization of the silicic acid is key in preventing large precipitation of Si and Fe. Judging from the saturation indices for minerals commonly found in geothermal fields, the amorphous precipitates with high and low Si/Fe atomic ratios may be precursors of silica polymorph and nontronite as a Fe(III) silicate because they can be formed at R from 1 to 9.